Legenda Yeh Abang Dan Pura Nampusela Di Desa Padangan: Analisis Struktur, Fungsi, Dan Nilai - Windari Giri, Ni Luh Gede; Nala Antara, I Gde; Supatra, I Nyoman (Humanis; Vol 17 No 3 (2016), 2016)
This study examines the legend of Yeh Abang and Pura Nampusela. The purpose of this research is to be able to describe the structure, function, and value in the Legend Yeh Abang and Pura Nampusela so it can be used as a guide to the behavior of people, especially people of Bali. Grounding theory used in this research is the structural theory, function, and value. Used structural theory based on the theory of Teeuw, Sukada, and Nurgiyantoro. For the analysis of the functions and values ??guided by the theory of functions and value delivered by Teeuw, Ratna, and Yudibrata. The method used in procuring data that observation and interview methods are supported with recording techniques as well as recording. In the data processing method used is descriptive-analytic and presentation of data analysis using informal methods. The results obtained in this study is a narrative structure that consists of: incidents, plot, character and characterization, setting, theme, and mandate. That the functions contained religious function, social function and the function of education is closely related to the situation of the villagers Padangan. And contains values ??of religious, ethics, magical value, social value and educational value.